2021
DOI: 10.1021/acsami.1c09677
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Photochromic Polymer Nanoparticles Based on Matrix-Dependent Förster Resonance Energy Transfer and Aggregation-Induced Emission Properties

Abstract: Dynamic color-tunable fluorescent materials are soughtafter materials in many applications. Here, we report a polymeric matrix-regulated fluorescence strategy via synergistically modulating aggregation-induced emission (AIE) properties and the Forster resonance energy transfer (FRET) process, which leads to tunable dynamic variation of color and photoluminescence (PL) intensity of fluorescent polymeric nanoparticles (FRET-PNPs) driven by photoirradiation. The FRET-PNPs were prepared via a facile one-pot miniem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…All of the fluorescent compounds were synthesized via the protocols reported in our previous work. , For the synthesis of TPE-PBE, TPE-B was first coupled with the Suzuki–Miyaura reaction to gain the phenolic derivative TPE-P, and then the hydroxyl group was substituted by 4-bromo-1-butene to give TPE-PBE (Scheme S1). In addition, (R/S)-2-(3′,3′-dimethyl-6-nitro-3′H-spiro-[chromene-2,2′-indol]-1′-yl) ethanol (SPOH) was synthesized with 5-nitrosalicylaldehyde and a bromide salt that was obtained by a quaternary ammonium of 2,3,3-trimethyl-3 H -indole and 2-bromoethanol, and then SPOH was modified with acryloyl chloride to obtain SPEA (Scheme S2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All of the fluorescent compounds were synthesized via the protocols reported in our previous work. , For the synthesis of TPE-PBE, TPE-B was first coupled with the Suzuki–Miyaura reaction to gain the phenolic derivative TPE-P, and then the hydroxyl group was substituted by 4-bromo-1-butene to give TPE-PBE (Scheme S1). In addition, (R/S)-2-(3′,3′-dimethyl-6-nitro-3′H-spiro-[chromene-2,2′-indol]-1′-yl) ethanol (SPOH) was synthesized with 5-nitrosalicylaldehyde and a bromide salt that was obtained by a quaternary ammonium of 2,3,3-trimethyl-3 H -indole and 2-bromoethanol, and then SPOH was modified with acryloyl chloride to obtain SPEA (Scheme S2).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the previous section, the dynamic fluorescence behavior of CS-FPNPs is a complicated result of TPE emission, reversible photoisomerization of SP and MC units, MC emission, and FRET process of TPE and MC units. It has been reported that the TPE emission and reversible photoisomerization of SP and MC units highly depend on the polymer matrix structure . For example, the rigid polymer matrices promote the TPE emission, but retard the ring-opening reaction of SP to MC units.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations